2017
DOI: 10.17843/rpmesp.2017.343.2425
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de las nanopartículas industriales TiO2, SiO2 y ZnO sobre la viabilidad celular y expresión génica en médula osea roja de Mus musculus

Abstract: RESUMENObjetivos. Evaluar el efecto de las nanopartículas de ZnO, TiO 2 y SiO 2 sobre la viabilidad celular y la expresión génica de las interleuquinas 7 y 3 y del factor estimulante de colonias de granulocito -macrófago (GM-CSF) en Mus musculus. Materiales y métodos. Se extrajo médula ósea roja de cinco roedores (Balb/c) para el estudio de viabilidad celular mediante la prueba de MTT. Por otro lado, grupos cinco roedores fueron inoculados vía intraperitoneal con dosis de 0,5; 1; 2,5; 5 y 10 mg/kg de nanopartí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…At 200 µg•mL −1 , Fe 2 O 3 and TiO 2 NPs reduced colony formation about 52.4% and 71.6%, respectively, indicating the highest inhibitory effect for TiO 2 NPs. In line with our finding, Zarria-Romero et al 30 was found that treatment with TiO 2 (45 ± 10.0 nm) and SiO 2 (12 ± 7.0 nm) NPs caused a decrease in the expression of granulocyte macrophage colony-stimulating factor (GM-CSF) in red bone marrow of Mus musculus.…”
Section: Discussionsupporting
confidence: 92%
“…At 200 µg•mL −1 , Fe 2 O 3 and TiO 2 NPs reduced colony formation about 52.4% and 71.6%, respectively, indicating the highest inhibitory effect for TiO 2 NPs. In line with our finding, Zarria-Romero et al 30 was found that treatment with TiO 2 (45 ± 10.0 nm) and SiO 2 (12 ± 7.0 nm) NPs caused a decrease in the expression of granulocyte macrophage colony-stimulating factor (GM-CSF) in red bone marrow of Mus musculus.…”
Section: Discussionsupporting
confidence: 92%
“…These data implied that ZnO-NPs enter the body, are distributed throughout the body, and elicited cytotoxicity in different animal organs (Li et al 2012 ). This outcome agreed with Zarria-Romero et al ( 2017 ), who found that ZnO-NPs (1–10 mg/kg) reduced cell viability in bone marrow cells of mice using MTT assay during 30 h from intraperitoneal inoculation. Further, the cytotoxic potential of ZnO-NPs has been documented in mouse bone marrow mesenchymal stem cells (Syama et al 2014 ), and human blood cells (Shalini et al 2018 ) using MTT assay.…”
Section: Discussionsupporting
confidence: 91%